2021
DOI: 10.1021/acschembio.1c00524
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Cyclic Cystine Knot Structural Motif for Immunosuppressive Effects of Cyclotides

Abstract: The cyclotide T20K inhibits the proliferation of human immune cells and is currently in clinical trials for multiple sclerosis. Here, we provide novel functional data and mechanistic insights into structure–activity relationships of T20K. Analogs with partial or complete reduction of the cystine knot had loss of function in proliferation experiments. Similarly, an acyclic analog of T20K was inactive in lymphocyte bioassays. The lack of activity of non-native peptide analogs appears to be associated with the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…72,83,88,[97][98][99] The CCK motif serves to effectively stabilize the structure of the cyclotide, thereby preventing any potential structural rearrangement that may occur upon interaction with receptors. 100 Some studies have also shown that cyclotides are highly toxic in the early stages of the insect's life cycle, the juvenile phase contributing to great devastation on the flora when they need a lot of nutrients to mature. In H. armigera larvae, the larval response to cyclotideinduced midgut cell damage is to increase the number of basal stem cells, which are responsible for replacement and repair during infancy.…”
Section: Membrane-acting Of Cyclotidementioning
confidence: 99%
“…72,83,88,[97][98][99] The CCK motif serves to effectively stabilize the structure of the cyclotide, thereby preventing any potential structural rearrangement that may occur upon interaction with receptors. 100 Some studies have also shown that cyclotides are highly toxic in the early stages of the insect's life cycle, the juvenile phase contributing to great devastation on the flora when they need a lot of nutrients to mature. In H. armigera larvae, the larval response to cyclotideinduced midgut cell damage is to increase the number of basal stem cells, which are responsible for replacement and repair during infancy.…”
Section: Membrane-acting Of Cyclotidementioning
confidence: 99%
“…Prominent among them is the nature-inspired T20K kalata B1, originally characterized from the African traditional plant Oldenlandia affinis . This knottin-like cyclotide has demonstrated therapeutic promise in inflammatory-related and autoimmune disorders [ 13 , 120 ]. A linear knottin, bevuTI-I, isolated from the aqueous extracts of Beta vulgaris , showed interesting mammalian enzyme inhibitory activity against trypsin (IC 50 = 471 nM) and human prolyl oligopeptidase (IC 50 = 11 μM), a drug target for neurodegenerative and inflammatory disorders [ 13 ].…”
Section: Limitations To the Pharmaceutical Applications Of Knottin-ri...mentioning
confidence: 99%
“…In a recent interesting report, the immunosuppressive propensity of a cyclotide T20K and its analogs are explored. The analogs of T20K, with partial or total reduction of the cystine linkages of the CCK motif are found to lose all of their function as shown in human immune cell proliferation experiments 15 …”
Section: Introductionmentioning
confidence: 99%
“…The analogs of T20K, with partial or total reduction of the cystine linkages of the CCK motif are found to lose all of their function as shown in human immune cell proliferation experiments. 15 In many organisms, the presence of interpenetrating disulfide bond scaffold, the "cystine knot" is noticed, primarily among peptides and proteins which include growth factors and toxins. [16][17][18][19] However, in cyclotides, the knot is specifically placed within a macrocyclic peptide backbone, thereby forming the CCK motif.…”
Section: Introductionmentioning
confidence: 99%